Kajian Doa Menurut Alkitab dan Relevansinya Dalam Kehidupan Kekristenan - Yosef, Hery Budi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This study discusses prayer from a Christian perspective, focusing on how and why Christians need to pray based on biblical teachings. The research method used is a literature study. Each piece of literature is analyzed with a focus on the topic of prayer in the Bible, as well as the writings of church history figures regarding the importance and nature of prayer practice. The study's results indicate that prayer in Christianity is not a tool to manipulate God or force Him to do something for His people. Prayer should not be naturalistic and artificial (instrumental) but must be sincere and based on the Bible. This study concludes that prayer in Christianity should be understood as sincere communication with God, strengthening both personal and collective relationships with Him.